Environmental regulations: Lessons from the command-and-control approach - Puja Singhal (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Policy makers have long favored command-and-control (CAC) methods to tackle environmental damage. The number of CAC policies devoted to environmental protection has increased steadily since the 1950s and have been a large part of the overall portfolio of environmental laws and regulation in the industrialized world. Schmitt and Schulze (2011) document that between 1970 and 2011 the two most prevalent EU air-pollution control instruments were CAC in nature. Over 50% of the policy instruments were of the CAC type (regulatory, interventionist, and top-down), with emission limits and technical requirements playing the role of the top two. In China and India, most of the environmental legislation also take the form of explicit directives that levy restrictions on both mobile (vehicular) and stationary sources (factories and combustion plants) of pollution (see Tanaka 2014, Greenstone and Hanna 2014).In the last two decades, there has been a notable increase in research evaluating policy and programs for environmental protection. The design of empirical studies emphasizes causal inference by comparing group of regulated (treated) firms with a comparable control group of firms that were not subject to the treatment. As a result, we now have an improved perspective on the causal effects of environmental policy instruments that address industrial pollution. This review discusses some of the implementation details of prominent CAC type regulations and highlights the lessons learned from the empirical evaluation of these initiatives.
Keywords: 330